1999
DOI: 10.1016/s0736-5748(98)00066-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2 purinoceptors in the regulation ofdna synthesis in the neural retina of chick embryo

Abstract: The activation of P2 purinoceptors induces Ca2+ mobilization in the early embryonic chick neural retina. This purinergic Ca2+ response declines parallel with the decrease in mitotic activity during retinal development. To investigate the role of P2 purinoceptors in the regulation of retinal cell proliferation, we studied the effects of the P2 purinoceptor antagonists suramin and pyridoxalphosphate-6-azophenyl-2',4'-disulphonic acid (PPADS), and of the agonist ATP on DNA synthesis in retinal organ cultures from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
3
44
0
1
Order By: Relevance
“…With regard to retinoblast proliferation and cell cycle progression, it has been demonstrated that ATP, released from the RPE, can nonautonomously modulate the rate of the retinoblast cell cycle and thereby regulate overall rates of eye growth (Martins and Pearson, 2008;Pearson et al, 2002;Pearson et al, 2005). Using chicken retinal explants and pharmacological manipulations, ATP was shown to mechanistically act by modulating the rate of mitosis (Pearson et al, 2002) and/or the rate of DNA synthesis (Sugioka et al, 1999;Pearson et al, 2005). Given the key enzymatic roles that the proteins encoded by the gart, paics and adss loci play in the biosynthesis of ATP, the most parsimonious explanation for the cellular mechanism underlying the microphthalmia observed in gart, paics and adss zebrafish mutants and/or morphants is that, in the absence of sufficient ATP, DNA synthesis during S phase is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to retinoblast proliferation and cell cycle progression, it has been demonstrated that ATP, released from the RPE, can nonautonomously modulate the rate of the retinoblast cell cycle and thereby regulate overall rates of eye growth (Martins and Pearson, 2008;Pearson et al, 2002;Pearson et al, 2005). Using chicken retinal explants and pharmacological manipulations, ATP was shown to mechanistically act by modulating the rate of mitosis (Pearson et al, 2002) and/or the rate of DNA synthesis (Sugioka et al, 1999;Pearson et al, 2005). Given the key enzymatic roles that the proteins encoded by the gart, paics and adss loci play in the biosynthesis of ATP, the most parsimonious explanation for the cellular mechanism underlying the microphthalmia observed in gart, paics and adss zebrafish mutants and/or morphants is that, in the absence of sufficient ATP, DNA synthesis during S phase is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, ATP has been suggested to act as a signaling molecule (Perez et al, 1988) being involved in early retinal development (Sugioka et al, 1999) and in neuronal information processing of the mature retina (Neal and Cunningham, 1994). Therefore, extracellularly released ATP may be involved in neuron-to-glia signaling in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological function of cP2X 4 receptors in embryonic skeletal muscle remains to be elucidated. In embryonic chick neural retina, ATP receptor was reported to regulate the synthesis of DNA [Sugioka et al, 1999]. It is not clear whether P2X4 receptor is involved in such a process, although cP2X 4 RNA is highly expressed in embryonic chick retina.…”
Section: Discussionmentioning
confidence: 99%